Analisis Pemeliharaan Menggunakan Metode Reliability pada Sistem Gas Turbine Engine untuk Mengetahui Kinerja Engine Turbofan CFM56-3 pada Pesawat Boeing 737-500 - Asrul Sani; Reo Yudhono; Arfie Armelia Erissonia (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
In carrying out structured maintenance, a method is needed to increase the durability of an aircraft component, one of the methods used is the reliability method. The reliability of aircraft components is very necessary to ensure that each aircraft component is serviceable and runs according to its function in the aircraft system, so to increase the reliability of an aircraft component, the reliability method is very important to do. This study aims to determine the critical life time limit of the asset or system or equipment function and identify the failure mode that occurs in the Gas Turbine Engine component of the Boeing 737-500 aircraft because if this engine fails, it can result in flight delays and if not handled immediately can cause the aircraft to experience Aircraft on Ground (AOG) conditions, because it has the potential to disrupt airworthiness and threaten safety. This study uses exploratory research which aims to simplify problems to make them easier to solve. This study uses the Pareto diagram method to determine the highest type of failure in components, then analyzes it using the failure mode effect analysis (FMEA) method. Based on FMECA and FTA analysis, there are 3 failure modes, the failure modes include mechanical system (Bleed Valve), pneumatic system (Butterfly Shaft), electrical system (actuator). The failure was due to the occurrence of the top event part consumable, namely the bleed valve part with an RPN value of 192, followed by the butterfly shaft part with an RPN value of 75 and the Actuator part with an RPN value of 72. The pneumatic system and electrical system categories are prioritized to carry out preventive maintenance, which means it is a solution from industry players in an effort to maximize maintenance of the turbofan engine system accompanied by technical or economic analysis to ensure a system in extending the service life of parts in the aircraft system.